Ex-post evaluation of public investments in infrastructures: how to foster economic development and ensure social equity - Emília Malcata Rebelo (2010)
In Europe in general and in Portugal, in particular, the performance and financial control over investments framed by European funding programmes has been strictly monitored in different moments, for each specific project. This shapes an ongoing control in relation to ex-ante settled goals, and are applied to the entities responsible for the reception and application of funds. This individual short-term assessment blurs a strategic assessment of economic, social and environmental impacts on true beneficiaries of performed aggregated regional investments: the general population, especially the most straightly affected by those investments. Additionally, considering the globalization and widespread competition processes, as well as the quick succession of both external and internal changes during a projects useful life, often the initial stated assumptions and goals cease to be a strong valid reference. This article aims at overcoming this flaw in the analysis, thus enabling the assessment of how past aggregated investments in infrastructures implies a sustainable economic development, and to what extent they are able to shrink inter-regional disparities. This analysis holds two aspects: the compared evolution of some macroeconomic issues among different regions, and the proper evolution of the economic performance of a certain region. But these kinds of analysis require from the beginning a strong management information system that enables the characterization of the regional situation, and that additionally includes the changes that take place in the meantime. The research reported in this article, applied to the Portuguese northern region, is supported on the application of mathematical tools that enable the analysis and assessment of ex-post regional benefits that accrue from public aggregated investments, in order to support the settlement of rules for the transparent and efficient use of public money.